PERANCANGAN RANGKAIAN PENGUAT DAYA DENGAN TRANSISTOR: Tasdik Darmana, Tony Koerniawan - Jurnal, Redaksi Tim (SUTET, 2018)
The power amplifier circuit is a circuit used to amplify or magnify input signals. The use of a transistor as an amplifier is that the current on the base is used to control the larger current given to the collector through the transistor. The small current change on the controlling base is what is called a large change in the current flowing from the collector to the emitter. The advantages of the amplifier transistors can not only amplify the signal, but these transistors can also be used as current amplifiers, voltage amplifiers and power amplifiers.